(untitled) (Journal of the College of Basic Education, 2022)
Field study was conducted in the fields of Gollege of Agriculture to evaluate the effect of three acaricides on the two spotted spider mites Tetranychus urticae Koch and the Coccinellidae predators. Results indicated that the acaricide Ortus was the most effective against all stages of mite followed by Oberon and then Abamactin. Mortality percentages for adults were 76.9, 73.4, and 69.8% recorded for three pesticide respectively. Mortality percentags were 79.6, 76.2 and 73.3% for moving immature stage . As for eggs stage Oberon was the most effective followed by Ortus and then Abamactin ware 74.5, 69.0 and 66.4% respectively after four weeks. Results also showed that The pesticide Ortus showed some harmful effects on Coccinellidae predators. Followed by Oberon, while Abamectin was relatively harmless. Aduls of the predators were less sensitive to the three acaricides than the other stages. Mortality percentages were 1.9 ,1.6 and 0.7 recorded after three weeks of treatment for intended acaricides respectively. Therefore, the application of the integrated management to control this pest should take in consideration the choice of the effective acaricides such as Abamectin with less toxicity to the predators and other natural enemies in the same time.